The Design of Website-Based Mosque Information System: A Case Study of Al-Muhajirin Mosque In Balongsari Using The Method of Rapid Application Development - Dheny Novaris Maulana; Alexander Wirapraja; David Saputra Octadianto Soedargo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Al-Muhajirin Balongsari Mosque in Surabaya still faces obstacles in managing information and finances because administrative processes are carried out manually, which can potentially lead to recording errors, loss of archives, delays in information delivery, and limited access for worshippers to activity and financial data. This study intends to design and develop a web-based Mosque Management Information System to facilitate integrated data management. The system development employs the Rapid Application Development (RAD) methodology to ensure a swift, iterative process aligned with user requirements. The proposed system includes management of agendas/activities, income, expenses, donations/transfers, transaction categories, galleries, and reporting, with access rights based on user roles: admin, officer, and congregation. The system architecture is depicted using Data Flow Diagrams (DFDs), Entity-Relationship Diagrams (ERDs), Conceptual Data Models (CDMs), and Physical Data Models (PDMs) to ensure data connectivity and transaction fidelity. The implementation results indicate that administrators can oversee officer and category data and generate reports; officers can enter transactions, verify transfers, manage agendas and galleries, and compile reports; while congregants can access activity information, prayer schedules, financial data, and donation services online. Based on functional testing of the administrator, officer, and user modules, the main features run as expected and produce valid outputs, indicating the system is capable of improving the efficiency, transparency, accountability, and accessibility of administrative management and the delivery of mosque information to congregants.